UPAYA MENINGKATKAN HASIL BELAJAR SERVIS ATAS BOLA VOLI MELALUI METODE DRILL PADA PESERTA DIDIK KELAS V - Yatim, Muhammad; Triansyah, Andika; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:This thesis entitled "Efforts to Improve Learning Outcomes of Volley Ball Through Drill Methods In Class V Participants". Using Action Research Methods. The results of this study From all the implementation of action research class in Class V SDN 11 Sungai Kakap Kabupaten Kubu Raya. The results of research: 1) Based on the observation of the learning activity seen that students become active and not quickly saturated in learning. The percentage increase in learning activity in cycle 1 reaches 72%, cycle 2 reaches 90%, while the expectation score is learning activity is 90%. This means the target of the learning activity has been reached. 2.0 Based on the evaluation results on the 1st cycle of the service ability of the students experienced an improvement from the initial conditions are: in the initial condition the number of students who reached the value of 75 new 3 students (20%) and in cycle 1 increased to 7 students (46.66%), then in cycle 2, increased to 14 students who achieved a score of 75 or more. This means the target 90. of the number of students reaching KKM with a value of 75 has been achieved.         Keywords:  Top Service, Volleyball, Drill Method.